Transgredience in Toward Debesija by Bronius Radzevičius - Grigaitis, Mindaugas (Respectus Philologicus, 2012)
The aim of this article is to present the transgredience theory of Russian scientist Mikhail Bakhtin as a compromise of the traditional and postmodern views of literature. Traditional criticism, which here is defined as a metaphysical view of literature as a subject’s self-representation, rejects the postmodern idea of the subject’s death as nihilistic blather. On the contrary, the postmodern attitude denies the subject’s identity as a centre of literature. The theory of transgredience admits that subjectivity is not dead, but rejects it as a constant and finite identity. It makes it possible to join the traditional and postmodern attitudes.The first section deals with these aspects of transgredience. Such categories as time, space, author, hero, exteriority, and inner world are defined. It is stressed that the word man, which traditionally is understood as a subject of constant identity, in Bakhtin’s theory means the possibility to create that identity. This possibility becomes aesthetic reality only when an author—the  principle of organizing language—exteriorizes and, through exteriorization, materializes experience in a hero. Exteriorization and the separation of man-authorhero are stressed as the main aspects of the theory of transgredience.The forms of transgredience that are expressed in Radzevičius’s novels are analyzed in the second section. The texts of this author come into the center of analysis because of their intensive correlations of experience and language. It is considered that the best way to present the theory of transgredience as a compromise of traditional and postmodern thought is to use it in an interpretation of the texts of those authors who not only join experience and language into an intense unity, but even feel the boundaries of representing experience through language. Radzevičius is one of those authors.Even though Lithuanian literary critics sees him as a master of creating unity between word and feeling, his texts, as a separate world which is governed by the rules of language, reveal that sometimes feeling absorbs language and novels becomes non-esthetic acts. Such situations are called disturbance of transgredience and have two directions: a) hero absorbs author and becomes an author of his own; b) author absorbs hero and makes him a figure of representing the ideology of the author as a living person. Both directions are described through analyses of certain novels.
Keywords: transgredience; Mikhail Bakhtin; Bronius Radzevičius; author; hero; artificial unity